1983
DOI: 10.1152/ajpregu.1983.245.2.r287
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration induces sodium depletion in rats, rabbits, and sheep

Abstract: The effect of water deprivation for 1 day on Na balance was measured in rats, rabbits, and sheep. In all three species, dehydration induced a considerable increase in the daily output of Na in urine. This resulted in the water-deprived animals becoming Na depleted as well as water deficient. Experiments were also designed to control for the reduced food intake that results from water deprivation in rats and rabbits. The results showed that decreased food intake was not the cause of the natriuresis and subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
52
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 0 publications
11
52
1
Order By: Relevance
“…It has been suggested that elevated plasma sodium concentration prevents the rise in aldosterone during dehydration to avoid augmenting the osmotic load. In addition, the osmotic load can be diminished by natriuresis, which has been observed in dehydrated animals in positive sodium balance (28,41). The present camels lost sodium via the milk and possibly also by natriuresis.…”
Section: Discussionmentioning
confidence: 55%
“…It has been suggested that elevated plasma sodium concentration prevents the rise in aldosterone during dehydration to avoid augmenting the osmotic load. In addition, the osmotic load can be diminished by natriuresis, which has been observed in dehydrated animals in positive sodium balance (28,41). The present camels lost sodium via the milk and possibly also by natriuresis.…”
Section: Discussionmentioning
confidence: 55%
“…Dehydrated animals show excessive drinking rapidly (Thracher et al, 1981;McKinley et al, 1983), and this rapid effect also occurs when animals drank hypertonic NaCl solution (Holmes and Gregersen, 1950). Increases in plasma osmolality reflected by plasma Na + levels ([Na + ]) cause proportional increases in water intake in animals (Fitzsimons, 1963).…”
Section: General Introduction Thirst and Salt Appetite Are Controlledmentioning
confidence: 99%
“…Increased plasma osmolarity may be a cause and/or a target of up-regulated renal f(P)RR in both the high salt intake and dehydration. It was reported that dehydration induced a considerable increase in the daily output of sodium in urine (McKinley et al 1983). Food and sodium intake fell during dehydration, but urinary sodium excretion increased significantly (Thrasher et al 1984).…”
Section: Discussionmentioning
confidence: 99%